Topical Mitomycin C and Radiation Induce Conjunctival DNA-Polyploidy - Olaf Cartsburg; Christopher Kallen; Jost Hillenkamp; Rainer Sundmacher; Natalia Pomjanski; Alfred Böcking (Analytical Cellular Pathology)
Introduction: Atypical cell changes often occur following treatment of premalignant or malignant conjunctival neoplasias with topical mitomycin C (MMC) and/or radiation. These reactive, non‐neoplastic alterations of the conjunctival epithelium can be a differential diagnostic problem. Our aim was to investigate changes in the nuclear DNA‐distribution of conjunctival epithelial cells after MMC‐ and radiation therapy by DNA‐image‐cytometry. Methods: Conjunctival brush smears were obtained from 13 patients (13 eyes) with squamous cell carcinomas and six patients (6 eyes) with conjunctival malignant melanomas in situ before, during and after treatment. The patients were treated with MMC‐drops (0.02% or 0.04%) alone (n=12), with radiation therapy (n=3) or both (n=4). At first, the obtained brush smears were evaluated by cytology. Secondly, after Feulgen restaining, the DNA content of reactively changed cells was determined using the AutoCyte‐QUIC‐DNA® workstation. Results: We observed euploid DNA‐polyploidy and cytomorphological changes in all patients (19/19). We considered these alterations as reactive to treatment. Four patients showed their greatest DNA‐stemline at 4c and 15 patients at 8c. This effect was observed during and following MMC‐drops and/or radiation and remained stable in 94% of all patients after a mean follow‐up of 22.5 months (SD 15.4). In five cases image cytometry additionally demonstrated DNA‐stemline aneuploidy as an evidence of tumor recurrence. Conclusion: Measurements of DNA‐content revealed euploid polyploidisation of morphological suspicious but benign squamous cells which is the biologic correlate of well known secondary morphologic changes following topical chemotherapy and/or radiation. DNA‐image‐cytometry is a useful tool in the differention of euploid polyploidization as a sign of reactive cell changes following treatment and tumor recurrences.